Clinical trial design for neuroprotection in RHO autosomal dominant retinitis pigmentosa; outcome measure considerations. (4th March 2021) - Otte, Benjamin; Andrews, Chris; Lacy, Gabrielle; Branham, Kari; Musch, David C.; Jayasundera, Kanishka T.
ABSTRACT: Purpose : To identify structural and functional outcome measures among patients with Rho-positive autosomal dominant Retinitis Pigmentosa (adRP) to aid neuroprotection trial design. Methods : This was a retrospective cohort study of 52 patients with Rho-positive adRP. We measured Goldmann Visual Fields (GVF) constriction in four sectors (nasal, temporal, inferior, superior), and sectoral Ellipsoid Zone (EZ) width degeneration using Spectral Domain Optical Coherence Tomography (OCT) scans. Disease progression trajectories were projected using mixed effects modeling. Results : Superior GVF was most constricted at presentation and had the shallowest trajectory (less steep negative slope); Inferior GVF was less constricted (corrected p < .001) and had a steeper negative slope (corrected p = .019) than superior GVF. Temporal EZ was most stable on OCT with a relatively shallow negative trajectory (corrected p = .011). Conclusions : Patients' superior visual fields presented with more constriction and subsequently had a shallow negative slope suggesting the corresponding inferior retina may be "burned out" at presentation. Targeted therapies for adRP will likely show a greater efficacy signal if delivered to the superior and nasal retina, which may demonstrate more change on OCT and GVF over the course of a neuroprotection trial. Translational Relevance : Mixed effects analysis of sectoral visual field constriction and EZ degeneration in Rho-positive adRP can prove useful in monitoring therapeutic efficacy and identifying targets for local therapies.